Biogenese und Autophagie des Endoplasmatischen Retikulums - Schäfer, Jasmin; Schuck, Sebastian (Biospektrum, 2017)
Adaptation to changing physiological conditions requires continuous adjustment of endoplasmic reticulum (ER) capacity. Cells have evolved elegant mechanisms to enlarge and shrink their ER according to need. An ER-localized monitoring system senses insufficient protein folding capacity and activates ER biogenesis to expand the organelle. Furthermore, cells dispose of excess or damaged ER by selective autophagy (ER-phagy). Together, these mechanisms ensure ER homeostasis and proper cell function.